-5(f+7)=3(3f+-1)

Simple and best practice solution for -5(f+7)=3(3f+-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(f+7)=3(3f+-1) equation:


Simplifying
-5(f + 7) = 3(3f + -1)

Reorder the terms:
-5(7 + f) = 3(3f + -1)
(7 * -5 + f * -5) = 3(3f + -1)
(-35 + -5f) = 3(3f + -1)

Reorder the terms:
-35 + -5f = 3(-1 + 3f)
-35 + -5f = (-1 * 3 + 3f * 3)
-35 + -5f = (-3 + 9f)

Solving
-35 + -5f = -3 + 9f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-9f' to each side of the equation.
-35 + -5f + -9f = -3 + 9f + -9f

Combine like terms: -5f + -9f = -14f
-35 + -14f = -3 + 9f + -9f

Combine like terms: 9f + -9f = 0
-35 + -14f = -3 + 0
-35 + -14f = -3

Add '35' to each side of the equation.
-35 + 35 + -14f = -3 + 35

Combine like terms: -35 + 35 = 0
0 + -14f = -3 + 35
-14f = -3 + 35

Combine like terms: -3 + 35 = 32
-14f = 32

Divide each side by '-14'.
f = -2.285714286

Simplifying
f = -2.285714286

See similar equations:

| -4(r+3)=-70 | | 3x+5+3x+5+x+x=66 | | 2x-6x+8x-9x= | | (2x+3)(x+5)= | | m^2-28m+25=0 | | 6k-k=27-4 | | 43(x-172)=86 | | 5x^2+34+24=0 | | w^2+17w+16=0 | | 3x+5+x=66 | | 0.20(x+10)+1.40x=66 | | 0.5(8w-6)=17 | | 5(-1.2)-y=4 | | 8w+3=6 | | 3*l=5 | | 4x-6+x=54 | | 5y+1+3y=-5 | | 4=16t-16t^2 | | 9-33=-4z | | -3x-4z=17 | | 5z^2-3x-2=0 | | 3(w-2)=6 | | 2x+3+x=54 | | w-3w=32 | | 2x+3=54 | | 0=-3x^2+2x+5 | | 4x-2(x+5)=-(2x+15) | | 4x-2(x+5)=-(2v+15) | | 3a+b=10 | | 3a-2b=-2 | | .75-9p=.60 | | 7x+9=3x-15 |

Equations solver categories